CITH-Garlic 1 : a new garlic variety - Singh, S R; Ahmad, N; Ranjan, J K; Mir, J I; Singh, D B; Jan, Nusrat (Indian Horticulture, 2019)
ICAR-Central Institute of Temperate Horticulture has developed a new long day variety of garlic â€œCITH-G-1â€ with high yield potential (474.36q/ha), larger clove size (4.5g) and resistance to major foliar diseases. The variety becomes ready to harvest in 210-245 days depending upon the altitude and time of planting. Due to its big size intact bulb, larger cloves and rich aroma the variety is highly preferred by the consumers and traders and fetch premium price in the market due to its harvesting in the end of June to first week of July which is the lean period of plains. On the basis of performance under multi-location testing this variety has been identified for agro climatic Zone I (Jammu and Kashmir, Uttarakhand, Himachal Pradesh).